A literature review of the therapeutic mechanisms of art therapy for veterans with post-traumatic stress disorder. Issue 2 (3rd May 2016) - Smith, Alison
ABSTRACT: Post-traumatic stress disorder in combat veterans is often managed with the use of psychological intervention such as Cognitive Behavioural Therapy (CBT) and Eye Movement Desensitisation and Reprocessing (EMDR). There is a body of evidence that suggests that some individuals do not respond as well as others to such interventions. Other strategies in use to support veterans in recovery include art-based therapies and anecdotal evidence suggests that these have therapeutic impact for veteran groups that do not benefit from the aforementioned psychological therapies. This article describes a review of the literature associated with art therapy with combat veterans, aiming to ascertain what the therapeutic mechanisms are for veterans in using art therapy to manage post-traumatic stress disorder symptoms. Themes became evident within the literature review that are discussed and analysed, with resultant ideas for future research possibilities identified.